2013
DOI: 10.1001/jamasurg.2013.1372
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Antibacterial Prophylaxis for the Prevention of Infectious Complications Associated With Tube Thoracostomy in Patients Undergoing Elective General Thoracic Surgery

Abstract: clinicaltrials.gov Identifier: NCT00818766.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Prophylaxis was not continued until removal of surgical drains during either time period, so we cannot comment on the impact of this practice from our analysis. It is worth noting that a recent randomised controlled trial (RCT) has not demonstrated any benefit for prolonged prophylaxis while thoracostomy tubes remained in situ …”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis was not continued until removal of surgical drains during either time period, so we cannot comment on the impact of this practice from our analysis. It is worth noting that a recent randomised controlled trial (RCT) has not demonstrated any benefit for prolonged prophylaxis while thoracostomy tubes remained in situ …”
Section: Discussionmentioning
confidence: 99%
“…This P value can be interpreted as a 26% chance that there would be results this extreme or more extreme if there was no difference between receiving the extended antibiotic prophylaxis as compared to the standard prophylaxis regimen in this study. The authors conclude that "extended postoperative antibacterial prophylaxis for patients undergoing elective thoracic surgery requiring tube thoracostomy did not reduce the number of infectious complications compared with preoperative prophylaxis only" (6). If the study calculated a P value of 0.01 for the difference in infectious complications between the two groups, a 1% chance that there was a observed difference that happened randomly between the treatments if there is not a true difference in infectious complications, researchers would reject the H 0 and state that there is a statistically significantly difference in infectious complications between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller the P value, the stronger the evidence against H 0 . For example, a recent trial evaluating extended postoperative antibiotic prophylaxis for elective thoracic surgery calculated a P value of 0.26 comparing patients receiving an extended antibacterial prophylaxis and those receiving standard preoperative prophylaxis only (6). This P value can be interpreted as a 26% chance that there would be results this extreme or more extreme if there was no difference between receiving the extended antibiotic prophylaxis as compared to the standard prophylaxis regimen in this study.…”
Section: Introductionmentioning
confidence: 99%
“…All patients in both the study groups received preoperative prophylaxis with cefazolin. The extended prophylaxis did not reduce the incidence of postoperative infections in the antimicrobial group as compared to placebo [30] . The overall incidence of complications (10% infections) was fairly high in this study when compared to earlier reports of medical thoracoscopy [4] .…”
Section: Discussionmentioning
confidence: 75%